Anthropogenic environmental drivers of antimicrobial resistance in wildlife - Swift, Benjamin M.C.; Bennett, Malcolm; Waller, Katie; Dodd, Christine; Murray, Annie; Gomes, Rachel L.; Humphreys, Bethan; Hobman, Jon L.; Jones, Michael A.; Whitlock, Sophia E.; Mitchell, Lucy J.; Lennon, Rosie J.; et al. (Elsevier, 2019)
The isolation of antimicrobial resistant bacteria (ARB) from wildlife living adjacent to humans has led to the suggestion that such antimicrobial resistance (AMR) is anthropogenically driven by exposure to antimicrobials and ARB. However, ARB have also been detected in wildlife living in areas without interaction with humans. Here, we investigated patterns of resistance in Escherichia coli isolated from 408 wild bird and mammal faecal samples. AMR and multi-drug resistance (MDR) prevalence in wildlife samples differed significantly between a Sewage Treatment Plant (STP; wastes of antibiotic-treated humans) and a Farm site (antibiotic-treated livestock wastes) and Central site (no sources of wastes containing anthropogenic AMR or antimicrobials), but patterns of resistance also varied significantly over time and between mammals and birds. Over 30% of AMR isolates were resistant to colistin, a last-resort antibiotic, but resistance was not due to the mcr-1 gene. ESBL and AmpC activity were common in isolates from mammals. Wildlife were, therefore, harbouring resistance of clinical relevance. AMR E. coli, including MDR, were found in diverse wildlife species, and the patterns and prevalence of resistance were not consistently associated with site and therefore different exposure risks. We conclude that AMR in commensal bacteria of wildlife is not driven simply by anthropogenic factors, and, in practical terms, this may limit the utility of wildlife as sentinels of spatial variation in the transmission of environmental AMR.